On the structure of continua with finite length and Gołąb's semicontinuity theorem. (April 2017) - Alberti, Giovanni; Ottolini, Martino
Abstract: The main results in this note concern the characterization of the length of continua 1  (Theorem 2.5 ) and the parametrization of continua with finite length (Theorem 4.4 ). Using these results we give two independent and relatively elementary proofs of Gołąb's semicontinuity theorem.